2000
DOI: 10.7748/ns2000.05.14.36.34.c2840
|View full text |Cite
|
Sign up to set email alerts
|

Organisational culture and consultant nurse outcomes: part 1 organisational culture

Abstract: Organisational culture is presented as a complex concept underpinned by specific values, beliefs and assumptions that account for the way things are done. Strong organisational cultures and a number of other attributes are highlighted as having influence on performance. The role of leadership is recognised as key to facilitating cultural change, as is the use of approaches which clarify values and highlight contradictions between espoused culture and culture in practice. A three-year study in which a consultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 5 publications
0
87
0
Order By: Relevance
“…Practice development should empower individuals and teams to understand what they do and how to improve patient care (Manley 2000, Manley andMcCormack 2003). These characteristics make graphic facilitation a valuable method in practice development with children's nurses.…”
Section: Online Archivementioning
confidence: 99%
“…Practice development should empower individuals and teams to understand what they do and how to improve patient care (Manley 2000, Manley andMcCormack 2003). These characteristics make graphic facilitation a valuable method in practice development with children's nurses.…”
Section: Online Archivementioning
confidence: 99%
“…'the way things are done around here' (Manley, 2000). As such, in order to transform mealtime care it is necessary to change the ward culture, which presents major challenges (Rycroft-Malone, 2004).…”
Section: Phase 2: Action Research To Change Practicementioning
confidence: 99%
“…Importantly, it has been suggested that culture in acute hospitals has the potential to influence service efficiency, equity considerations within organisational strategy, the overall economic and social objectives of the organisation, and co-operation and partnerships internal and external to the organisation (Manley, 2000). Research has also found that organisational culture may be a relevant factor in healthcare performance (Davies, Mannion, Jacobs, Powell, & Marshall, 2007;Manley, 2000;Page & Howell, 2015). It has been argued that culture at the individual, team, and organisational level creates the context for clinical practice (Manley, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also found that organisational culture may be a relevant factor in healthcare performance (Davies, Mannion, Jacobs, Powell, & Marshall, 2007;Manley, 2000;Page & Howell, 2015). It has been argued that culture at the individual, team, and organisational level creates the context for clinical practice (Manley, 2000). Within an organisation, however, several different (and sometimes conflicting) cultures with their own attitudes, beliefs, customs, values, and practices may exist, with the potential of suboptimal working relationships stemming from 'cultural clashes' (McCormack et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation